COLOUR-CODED FOR YOUR CONVENIENCE. SKEUOMORPHISM IN ROMAN POTTERY PRODUCTION IN GERMANIA INFERIOR - Geerts, Roderick C. A. (Rei Cretariae Romanae Fautorum Acta, 2022)
Skeuomorphism is, in short, a concept describing the manufacture of vessels in one material intended to evoke the appearance of vessels regularly made in another. The concept has been applied to archaeological objects since the late 19th century. Usually similarities between pottery and metal vessels have been the main focal point of the theory, in order to reconstruct the shape of metal tableware which is less likely to be recovered archaeologically. In this paper some case studies will be brought forward to illustrate the concept of skeuomorphism in Germania Inferior, mainly to analyse pottery and the many common shapes and colours being used throughout the province. Potters from various workshops take great effort to colour their pots correctly and to imitate already produced pottery or even metal vessels. This paper explores the interplay between locally operating potters and the larger production centers. Examining case studies from Germania Inferior shows that pottery from local production isn’t just about imitating the shape but also the colour of imported products from larger production centers in order to adhere to a standard and get their products sold.